How efficient is the Asian honey bee, Apis cerana in pollinating mustard, Brassica campestris var. toria? Pollination behavior, pollinator efficiency, pollinator requirements and impact of pollination. Issue 4 (8th August 2017) - Stanley, Johnson; Sah, Khushboo; Subbanna, Avupati R.N.S.
Abstract : Brassica campestris var. toria (mustard) is an insect attractive crop with ample pollen and nectar, so is predominantly insect pollinated. Rate of pollinator visitation, delivery of pollen to stigmas and seed-set are various factors to assess the importance of a pollinator. The Asian honey bee, Apis cerana was found to occupy a share of 39.33% of all the flower visitors to mustard in natural habitat. Pollination behavior in terms of peak activity, flowers handled per unit time, time spent per flower and time spent in search of flowers were studied separately for both pollen and nectar foragers. Pollination efficiency of A. cerana in mustard, measured by means of seed set per flower at defined number of bee visits was 0.41 and 2.44 visits per flower required for optimum seed set. Impact of A. cerana bee pollination on mustard seed production was studied in two different villages for two years. An increase of 20.8% in siliqua/panicle, 9.4% of seeds/siliqua and 17.1% in seed yield were noticed in planned honey bee pollinated mustard with respect to those grown in natural habitats. For assessing the requirement of pollinators to pollinate a one ha area of mustard, flower availability and the flower handling time of both the pollen and nectar forager are taken into consideration. A forager was estimated to pollinate 10, 146 flowers a day, but mustard needs 2.44 visits for optimum seed set. Thus, 1, 530 bee foragers or 2.2 colonies are needed to effectively pollinate a 1 ha mustard crop at peak flowering.